Unveiling the silent threat-understanding hypertension knowledge and perception among adults: review article - Muskaan; Sikka, Gitanjali; Shaveta (International Journal of Research in Medical Sciences, 2024)
Hypertension is major risk factor for cerebrovascular and cardiovascular diseases. Hypertension, characterized by persistently elevated blood pressure, has emerged as a modern- day epidemic, particularly alarming in developing countries. The classification outlined by the Joint National Committee report offers a framework for understanding its severity, ranging from normal to stage 2 hypertension. Notably, studies in regions like Punjab and Haryana highlight the need for tailored interventions and education of patients about the disease knowledge, its severity, and complications. The increasing global prevalence is which inherently increasing the global disease burden whereas knowledge of this disease and its determinants are poor. To evaluate the level of knowledge and perception about hypertension in population. Moreover, the variations in knowledge and perceptions of hypertension between rural and urban populations have yet to be examined. In order to fill this knowledge gap, the current study understanding perceptions and knowledge of hypertension.